(3GdGSJjYGH aj eYQaI GdCUMGHs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3bGd CHh YeQ GHf YHO GdHQ GdfeQi GdbQWHi QVi Gddg Yfg (B: (3HMeO Gddg CHJOi hHg CSJYjf s
(3BNQgG (B:s
(3jfJgi HJQLeI (B" (3fYje Hf gRGd GdGSdei (B: (3ef MQa Gdfhf hjdjg ai GdPi HYOg (B: (3fejQ s
(3hbO cJHJ QDhS GdJQGLe HNW cHjQ ZGjI ai GdMSf hGdEJbGfs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eMeO Hf jMi GdMOGOGdNGUg HeOjfg BH s
Keywords: (3GdJGQjNs